2016
DOI: 10.1002/adfm.201504949
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Stability Enhancement in Perovskite Solar Cells by Inserting Lithium‐Neutralized Graphene Oxide as Electron Transporting Layer

Abstract: wileyonlinelibrary.comthe theoretical values, [ 9 ] further work is needed to increase the fi ll factor (FF) that today remains the bottleneck for the PCE enhancement. In this context, the optimization of interfaces between absorber, carrier transport layers, and electrode contact layers is crucial for an effi cient carrier transport. Thus, to improve the PCE of the PSCs, three main aspects need to be taken into account: the band alignment, the interface structure, and its passivation. [ 9 ] Furthermore, it mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
178
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(187 citation statements)
references
References 51 publications
6
178
1
2
Order By: Relevance
“…The equivalent circuit used to fit the data is shown in the inset of Figure 2c. [43] Compared with the control perovskite film, 1 and 3 nm blue shifts are observed for MB 1.5 and MB 2.0 films, respectively. [39,40] From the fitting results in Figure S16 and Table S3 (Supporting Information), similar R s values of 10.1 and 10.2 Ω cm 2 are obtained due to the identical FTO and gold conductive electrode in two devices.…”
Section: Resultsmentioning
confidence: 88%
“…The equivalent circuit used to fit the data is shown in the inset of Figure 2c. [43] Compared with the control perovskite film, 1 and 3 nm blue shifts are observed for MB 1.5 and MB 2.0 films, respectively. [39,40] From the fitting results in Figure S16 and Table S3 (Supporting Information), similar R s values of 10.1 and 10.2 Ω cm 2 are obtained due to the identical FTO and gold conductive electrode in two devices.…”
Section: Resultsmentioning
confidence: 88%
“…Previously, Kamat and co-workers and Deng and and co-workers independently employed a CuI layer as a p-type hole conductor instead of the organic hole conductor (spiro-OMeTAD) or PEDOT:PSS in an n-i-p-type meso-PSC [24] or a p-i-n-type planar-PSC, [25] respectively. [2] It is noticed that Carlo and coworkers reported how PbI 2 at the interface between TiO 2 ETL and perovskites prevents the back-recombination, [27] and Qiao and co-workers reported how Li cation incorporated to neutralized graphene oxide between TiO 2 ETL and perovskites ETL improves electron extraction ability. [2] It is noticed that Carlo and coworkers reported how PbI 2 at the interface between TiO 2 ETL and perovskites prevents the back-recombination, [27] and Qiao and co-workers reported how Li cation incorporated to neutralized graphene oxide between TiO 2 ETL and perovskites ETL improves electron extraction ability.…”
mentioning
confidence: 99%
“…[14][15][16] However, all of the PCEs reported are limited to less than 14 % and the perovskite was not formed as a perfect film, which casts the doubt on the real beneficial role of rGO on high-efficiency PSCs. In contrast to many applications of carbon-based materials that are usually introduced at the perovskite/TiO 2 or perovskite/HTM interfaces, or in substitution of the HTM itself, [17,18] here we propose a systematic study by exploring three different configurations as shown in Figure 1.We integrated the rGO: 1) in the 2,2',7,7'-tetrakis(N,N'-di-pmethoxyphenylamine)-9,9'-spirobifluorene (spiro-OMeTAD) HTM, 2) in the matrix of the active perovskite layer, and 3) within the mesoporous TiO 2 (m-TiO 2 ) ETM. In this study, mesoscopic PSCs are composed of a fluorine doped tin oxide (FTO)-coated glass substrate, a compact TiO 2 layer followed by a m-TiO 2 layer, a mixed (FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.15 (FA = formamidinium, MA = methylammonium) perovskite layer that infiltrates into the m-TiO 2 , a spiro-OMeTAD layer, and a Au counter electrode.…”
mentioning
confidence: 99%
“…[14][15][16] However, all of the PCEs reported are limited to less than 14 % and the perovskite was not formed as a perfect film, which casts the doubt on the real beneficial role of rGO on high-efficiency PSCs. In contrast to many applications of carbon-based materials that are usually introduced at the perovskite/TiO 2 or perovskite/HTM interfaces, or in substitution of the HTM itself, [17,18] here we propose a systematic study by exploring three different configurations as shown in Figure 1.…”
mentioning
confidence: 99%